Traditional vs Online Games: Their Benefits for Young Learners - Suwastini, Ni Komang Arie; Radhaswati, I Dewa Ayu Agung; Jayantini, I Gusti Agung Sri Rwa; Artini, Ni Nyoman (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractAs young learners like to learn in a fun atmosphere with engaging interactions, the present study argues that when children learn English as a foreign language, implementing games in teaching English can benefit young learners. The research was conducted following the library research method, where the content of the research from previous studies on English for young learners and the benefits of using games in teaching English for young learners were collected with the keywords "young learners", "traditional games", and "online games." The sources were selected from articles published in reputable international and accredited national journals from 2010-2022. The result of this study shows that two types of games can be chosen such as traditional and online games. The implementation of each type of game in teaching has strengths, weaknesses, and suggestions to improve the quality to help young learners learn. Overall, young learners will get more positive impacts due to the implementation of both traditional and online games. They can be recommended as strategies to teach English to young learners.  AbstrakSebagai pembelajar muda yang suka belajar dalam suasana yang menyenangkan dengan interaksi yang menarik, penelitian ini berargumen bahwa ketika anak-anak belajar Bahasa Inggris sebagai bahasa asing, penggunaan permainan dalam pengajaran Bahasa Inggris dapat memberikan manfaat bagi pembelajar muda. Penelitian ini dilakukan mengikuti metode penelitian perpustakaan, di mana konten penelitian dari studi sebelumnya tentang Bahasa Inggris untuk pembelajar muda dan manfaat penggunaan permainan dalam pengajaran Bahasa Inggris untuk pembelajar muda dikumpulkan dengan kata kunci "pembelajar muda", "permainan tradisional", dan "permainan online". Sumber-sumber ini dipilih dari artikel yang diterbitkan dalam jurnal internasional terkemuka dan jurnal nasional yang terakreditasi dari tahun 2010-2022. Hasil dari penelitian ini menunjukkan bahwa dua jenis permainan dapat dipilih, yaitu permainan tradisional dan permainan online. Implementasi setiap jenis permainan dalam pengajaran memiliki kelebihan, kelemahan, dan saran untuk meningkatkan kualitasnya agar membantu pembelajar muda belajar. Secara keseluruhan, pembelajar muda akan mendapatkan dampak positif lebih banyak karena penggunaan baik permainan tradisional maupun online. Kedua jenis permainan ini dapat direkomendasikan sebagai strategi untuk mengajar Bahasa Inggris kepada pembelajar muda.How to Cite: Suwastini, Ni Komang A., Radhaswati, I Dewa A. A., Jayantini, I Gusti A.S.R., Artini, Ni Nyoman. (2023). Traditional vs Online Games: Their Benefits for Young Learners. TARBIYA: Journal of Education in Muslim Society, 10(1), 13-38. doi:10.15408/tjems.v10i1.31329.